The Effects of Income Smoothing, Earnings Persistence, Leverage, And Firm Size On Earnings Response Coefficient - Fatin Husna Amalia; Aulia Fuad Rahman (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
This research aims to prove the impacts of income smoothing, earnings persistence, leverage, and firm size on the earnings response coefficient among consumer non-cyclical companies listed on the Indonesia Stock Exchange during the 2020-2023 period. Using the purposive sampling technique, 46 companies were selected as the sample, resulting in 184 financial reports as the observation data. The results of the panel data regression lead to findings that earnings persistence and firm size positively influence the earnings response coefficient and that income smoothing and leverage do not impact the earnings response coefficient. These findings can be used by the companies as foundations for their effort to enhance transparency, earnings stability, and credibility in the market.